Pediatric Obstructive Sleep Apnea in High-Risk Populations: Clinical Implications - ElMallah, Mai (Pediatr Ann, 2017)
Certain common medical conditions are associated with a higher risk of pediatric obstructive sleep apnea (OSA). A lower threshold for screening is therefore indicated for such patient cohorts. In this article, we briefly discuss the high prevalence of OSA in children born prematurely, and in those with Down syndrome, craniofacial disorders, and neuromuscular disorders. Primary care providers should have an increased index of suspicion for OSA in these children, considering the neurocognitive disability that occurs in these high-risk groups when OSA is left untreated.